The Paradigm of Progressive Judge’s Decision and Its Contribution to Islamic Legal Reform in Indonesia - Fikriawan, Suad; Anwar, Syamsul; Ardiansyah, Misnen (Al-Manahij: Jurnal Kajian Hukum Islam, 2021)
All this time, both in academic discourse and the reality of legal practice in the field tend to show a lack of attention to the rule of judges as an instrument of legal reform. Generally, the law is regarded as the main instrument of legal reform. Therefore, instilling an understanding of the law enforcement officers, especially the judges through their decision, is a very urgent thing to do. The main issue to be discussed in this paper is: How is the contribution of the Judge's decision to legal reform in Indonesia? This study used the perspective of the School of Sociological Jurisprudence, mainly the philosophical mind of Roscoe Pound. The results of this study show that the effort to make a judge's decision as a means of legal reform is a necessity. This can be realized through a progressive legal paradigm. The presence of a progressive legal paradigm is very important in order to give birth to a progressive type of judge who has a legal decision that qualifies maturity of law. The product of a progressive judge's decision is expected to become a jurisprudence that can be used as a reference in solving the next case so that judges will be able to make the law, not merely as a tool of social control as well as a tool of social engineering. These conceptions of legal function are essentially about to reveal that the nature of the law is dynamic rather than static. The legal philosophy of the sociological jurisprudence school offers a holistic understanding and a holistic view of the law, that is, the law applied must pay attention to the values, the living law, and the local wisdom of society. This holistic understanding of the law will ultimately be able to unify the law and society as its sociological basis.